The Electronic Government Application Analysis Through the Regional Archives Information System (SIKD) Application - Mardiani, Lina; Suhartanti, Sita Wirantik; Khumayah, Siti; Rahmayanti, Rahmayanti (Jurnal Polisci, 2025)
Background. The Cirebon Regency Government applies the concept in the innovation of Digital Archive Management, known as SIKD (Regional Archives Information System). This innovation is one of the government's methods for managing archives using technology (e-government). Aims. The purpose of this study is to evaluate the implementation of SIKD, analyze how employees at the Regional Secretariat of Cirebon Regency apply this SIKD, identify the obstacles and challenges in implementing the SIKD application, and assess the impact of the SIKD application on administrative efficiency. Methods. The research method employed is qualitative descriptive, utilizing data collection methods that include interviews and documentation. Conclusion. In this study, the researcher applied Everett M. Rogers' Innovation Diffusion Theory by analyzing four main elements: innovation, communication channels, time, and social system. Implementation. Although the positive impact of SIKD is very real, several aspects need to be considered to ensure an optimal and sustainable implementation.